Non-Stop India - Tully, Mark (New Delhi Penguin Books, 2011)
Non-Stop India The much-anticipated follow-up to the bestselling No Full Stops in India now available in paperback! Poised to become one of the major economies of the twenty-firstcentury, India at times seems unmindful of questions on thesustainability of such growth and its effect on the stability ofthe nation. Veteran journalist and bestselling author of No FullStops in India, Mark Tully travels across India to turn thespotlight on the everyday concerns of the common man in areas suchas governance and business, spirituality and ecology. In revealinginterviews with captains of industry and subsistence farmers,politicians and Dalits, spiritual leaders and bandits, he capturesthe voices of the nation even as he celebrates its vibrant historyand incredible potential.
Include Map, Bibliography and Index.
Mark Tully Sir Mark Tully was born in Calcutta, India, in 1935. He was theChief of Bureau, BBC, New Delhi, for twenty-two years, was knightedin the New Years Honours list in 2002 and was awarded the PadmaBhushan in 2005. Today, his distinguished broadcasting careerincludes being the regular presenter of the contemplative BBC Radio4 programme Something Understood. His books include No Full stopsin India, The Heart of India, India in Slow Motion (written withhis partner and colleague Gillian Wright) and Indias UnendingJourney. He lives in New Delhi. Reviews Tully report s on the various Indias behind the headlines- Hindustan Times Through Tullys probing eyes, one discovers the complex workingsof the Indian democracy.
Keywords: India -- Social conditions -- Economic development